Spo0A regulates chromosome copy number during sporulation by directly binding to the origin of replication in Bacillus subtilis1. Issue 4 (21st January 2013) - Boonstra, Mirjam; de, Imke G.; Scholefield, Graham; Murray, Heath; Kuipers, Oscar P.; Veening, Jan‐Willem
Summary When starved, Bacillus subtilis cells can enter the developmental programme of endospore formation by activation of the master transcriptional regulator Spo0A. Correct chromosome copy number is crucial for the production of mature and fully resistant spores. The production and maintenance of one chromosome for the mother cell and one copy for the forespore requires accurate co‐ordination between DNA replication and initiation of sporulation. Here, we show that Spo0A regulates chromosome copy number by directly binding to a number of Spo0A binding sites that are present near the origin of replication (oriC). We demonstrate that cells lacking three specific Spo0A binding sites at oriC display increased chromosome copy numbers when sporulation is induced. Our data support the hypothesis that Spo0A directly controls DNA replication during sporulation by binding to oriC.